(untitled) (Medical Forum Monthly, 2024)
Objective: The primary objective of the present study was to determine whether in patients with prehypertension six months of treatment with an angiotensin II, type 1 receptor antagonist (at a dose of 8mg once a day) reduces the incidence of hypertension in borderline patients Study Design: Randomized, open-labeled, prospective study. Place and Duration of Study: This study was conducted in the department of pharmacology and therapeutics, Basic Medical Sciences Institute (BMSI), Jinnah Post Graduate Medical Centre (JPMC), Karachi, from July 2007 to January 2008. Materials and Methods: This study involved eighty untreated participants between 30 to 60 years of age of either sex with blood pressure on study entry in high-normal range i.e. systolic blood pressure of 130 to 139 mmHg and diastolic blood pressure of 85 to 89 mmHg, according to the classification developed by Joint National Committee on prevention, Detection, Evaluation, and Treatment of high blood pressure (JNC-VI). All participants were randomized and enrolled in study after baseline investigations and informed written consent. Results: All values have been expressed in standard error of mean (± SEM). Forty patients were treated with DR1 and DR2 from day 0 to day 90th of study period respectively. InDR1 group the mean systolic B.P was decreased from 138 mmHg to 125.8 mmHg from day 0 to day 90th. In DR2 group an increase was observed in systolic B.P from 128 mmHg to 136 mmHg from day 0 to day 90th. An average percentage decrease of 8.21 % in case of DR1 while, 5.52 % was increased in DR2 group. In same way a decrease of 11.82 % in DR1 group, while, an increase of 11.5 % was observed in case of DR2 group in mean diastolic blood pressure respectively from day 0 to day 90th of study duration. Conclusion: Treatment of prehhypertension with an angiotension receptor antagonist May decreases incident hypertension. Additional studies will be needed to ascertain whether this or other strategies involving early pharmacological treatment of prehypertension would positively affect clinical outcomes.